2005
DOI: 10.1111/j.1365-2656.2005.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Age at first breeding and fitness in goshawk Accipiter gentilis

Abstract: Summary1. Age at first breeding has a large influence on fitness and hence is crucial to the evolution of life-history strategies. Goshawks Accipiter gentilis start breeding aged 1-4 years. Using 30 years of data and both lifetime reproductive success (LRS) and λ ind as a fitness estimate for 74 female goshawks, I showed that the optimal age at first reproduction was 3 years in this population. 2. Females that started to breed earlier had lower LRS and λ ind , not because of reduced life span, but because of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 51 publications
4
125
1
1
Order By: Relevance
“…On the other hand, we also obtained support for the hypothesis of differential selection of goshawk phenotypes: those birds best able to catch pigeons when young tended to live longest (see figure 2b). Empirical data support the finding that differential recruitment and/or mortality patterns play a role in goshawks; recruitment age is known to vary in this species (review: Rutz et al in press), and mortality rates are comparatively high and decrease steeply with age (Bijlsma 1993;Kenward et al 1999;Krü ger 2005). We were unable to test the effort hypothesis (Forslund & Pärt 1995), because we lacked direct measures of individual hunting skills (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, we also obtained support for the hypothesis of differential selection of goshawk phenotypes: those birds best able to catch pigeons when young tended to live longest (see figure 2b). Empirical data support the finding that differential recruitment and/or mortality patterns play a role in goshawks; recruitment age is known to vary in this species (review: Rutz et al in press), and mortality rates are comparatively high and decrease steeply with age (Bijlsma 1993;Kenward et al 1999;Krü ger 2005). We were unable to test the effort hypothesis (Forslund & Pärt 1995), because we lacked direct measures of individual hunting skills (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…The method is routinely used in goshawk population studies (for further methodological details, see Kü hnapfel & Brune 1995;Rust & Kechele 1996;Bijlsma 1997), including those that are concerned with age-related trends in breeding performance (e.g. Nielsen & Drachmann 2003;Risch et al 2004;Krü ger 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although density-dependent effects have been recorded in many populations (for example, Jorgenson et al 1997;Bennetts et al 2000;Kruger 2005;Stewart et al 2005), effects in the red deer population of the North Block of the Isle of Rum, Scotland are particularly well characterized thanks to long-term monitoring of life histories. Previous work has shown that age at primiparity, birth date and inter-birth interval increased with population density, while female fecundity and calf over-winter survival declined (Clutton-Brock et al 1982;Kruuk et al 1999a;Clutton-Brock & Coulson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this increasing population, a possible explanation of deferred breeding may be related to the increase in density (Donázar et al 2005, Carrete et al 2006a, that could affect age at maturity (Krüger 2004).…”
mentioning
confidence: 99%